Input Selection Drives Molecular Logic Gate Design - Francielly T. Souto; Gleiston G. Dias (Analytica, 2023)
Optical detection devices have become an analytical tool of interest in diverse fields of science. The search for methods to identify and quantify different compounds has transposed this curiosity into a necessity, since some constituents threaten the safety of life in all its forms. In this context, 30 years ago, Prof. Prasanna de Silva presented the idea of sensors as Molecular Logic Gates (MLGs): a molecule that performs a logical operation based on one or more inputs (analytes) resulting in an output (optical modification such as fluorescence or absorption). In this review, we explore the implementation of MLGs based on the interference of a second input (second analyte) in suppressing or even blocking a first input (first analyte), often resulting in INHIBIT-type gates. This approach is interesting because it is not related to attached detecting groups in the MLG but to the relation between the first and the second input. In this sense, flexible and versatile MLGs can be straightforwardly designed based on input selection. To illustrate these cases, we selected examples seeking to diversify the inputs (first analytes and interfering analytes), outputs (turn on, turn off), optical response (fluorescent/colorimetric), and applicability of these MLGs.